EVALUASI STATUS KESUBURAN TANAH DAN USAHA PERBAIKAN DI DAS OBA KOTA TIDORE KEPULAUAN - Idris Abd Rachman; Amirudin Teapon (Universitas Khairun, 2016)
The Objectives of study were to find out some chemistry and physical soil conditions, to evaluate and map soil fertility status according to Cation Exchange Capacity (CEC), alkali solution (KB), C-organic and N, P, K unsure and to arrange the alternatives of soil management in improving limited factor of soil fertility. Data were collected for soil and physical environment on soil survey method with a fisiography approach which is to splite landscape on units of landform then to free survey the landform units. Field observation on soil identification was digging and fulfilling the profile scape. The chemical soil fertility is divided into three categories: (1) high fertility in organosol hemic (Histosol), (2) middle fertility in Rodik Mediteran (Alfisol), Mediteran Gleik (Alfisol), kambisol kromik (Inceptisol) and podsolic rodik (Ultisol) and (3) low fertility in kambisol gleik (Inceptisol), Podsolik Rodik-Ultisol and kambisol Eutrik-Inceptisol. Limited reclamation effort was calcium carbonat for improving pH and organic matter that be able to increase CEC, Kalium, and Phosphor. Whole mentioned above can improve the fertility unsure on soil. Key words : soil fertility, alternative management, Oba River Basin